Effective Methods of Using "Steam" Technology in Preschool Educational Organizations - Khudaykulov Shavkat Soyibjonovich; Abdullajonova G.A.; Khamidova R.N. (Euro Asian Journal Publishing, 2023)
This article explores effective methods for introducing STEAM (science, technology, engineering, art and mathematics) technologies into preschool educational organizations. It discusses the benefits of integrating STEAM into early childhood education, offers practical implementation strategies, presents results of successful implementations, and provides insight into the future of STEAM in early childhood education.
Keywords: STEAM technology; preschool education; early childhood education